ESTIMATING OF SOME GENETIC PARAMETERS IN BREAD WHEAT BY USING FACTORIAL MATING DESIGN - Ismail Hussain Ali (Mesopotamia Journal of Agriculture)
This study was carried out to estimate some genetic parameters in bread wheat, Six cultivars of bread wheat (male parents) ATTLA (1), MILAN (2), Acsad 8 (3), Acsad 17 (4), Noor (5) and Cross bred-6 were crossed during the season of 2008-2009 with three cultivars (female parents) by using factorial mating design. The eighteenth crosses were grown with their parents during the season of 2009-2010 in a Randomized Complete Block Design (RCBD) with three replications. Data were collected for plant height (cm), spike length (cm), spikes number/plant, grains number/spike, biomass yield/plant (g), grain yield/plant (g) and harvest index (%). The results showed significant differences among genotypes for all the traits studied, Positive general combiners for many traits were obtained with the best parents like 4, 2 and 1 which be used as important parents in hybridization program because of their ability to transmit their characteristics to their progenies. Many positive specific combiners having positive mid parent heterosis and derived from positive general combiners, were obtained such as 1×8, 1×9 and 3×7 which are important crosses for selection in segregation generations. The results showed also that dominance gene action controlled all traits except plant height and the character with mid narrow-sense heritability had positive relationship with grain yield.